2012
DOI: 10.2141/jpsa.0110133
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of Arginine Requirements for Broilers Exposed to Hypobaric Condition during the 3-to 6-week Period

Abstract: In order to estimate arginine (Arg) requirements of male broilers (Ross 308) during the 21-to 42-day period and exposed to hypobaric condition, six diets (200 g/kg CP and 13.4 MJ ME/kg) with graded levels of Arg (8.8 to 14.3 g/kg) were allocated to four pens of twelve birds each. Body weight gain, feed:gain, breast meat yield, plasma nitric oxide (NO) concentration, and right to total ventricular weight ratio (RV/TV) were determined as response criteria. Responses to Arg supply were nonlinear and attained plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…NO is a potent vasodilator that inhibits pulmonary hypertension (Khajali and Wideman, 2016). Basoo et al (2012) re-evaluated the ARG requirements for broilers raised at high altitude (2100 m) during a 3-to-6-week period. They estimated that the ARG requirement for maximal growth and prevention of pulmonary hypertension was 20% higher than that of NRC (1994) recommendation (1.32 vs. 1.1% of diet).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO is a potent vasodilator that inhibits pulmonary hypertension (Khajali and Wideman, 2016). Basoo et al (2012) re-evaluated the ARG requirements for broilers raised at high altitude (2100 m) during a 3-to-6-week period. They estimated that the ARG requirement for maximal growth and prevention of pulmonary hypertension was 20% higher than that of NRC (1994) recommendation (1.32 vs. 1.1% of diet).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that ARG supplementation of broiler diets significantly improved cardiopulmonary hemodynamics and reduced mortality from ascites (Wideman et al, 2013;Saki et al, 2013;Sharifi et al, 2015). It has been reported that ARG requirement for maximal growth and prevention of right ventricular hypertrophy was significantly greater than the requirement advocated by the National Research Council (NRC) (1994) (Basoo et al, 2012). In fact, dietary ARG requirements for broilers advocated by NRC may not be adequate to support maximal growth and immune function and to avoid pulmonary hypertension in broilers reared at high altitude (Izadinia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Supplemental dietary arginine tended to reduce the incidence of ascites in broilers exposed to cool temperatures in one experiment but not in another (Ruiz-Feria et al, 1999). Diets supplemented with arginine increased plasma NO levels and attenuated the reduced growth performance and symptoms of pulmonary hypertension in broilers exposed to the combined challenges of cool temperatures and hypobaric hypoxia (Khajali et al, 2011b;Basoo et al, 2012). A recent review of the interrelationships between dietary arginine and NO in poultry concluded that under certain environmental conditions dietary arginine may be limiting for optimal growth and immune competence, and that NO opposes the pathogenesis of PAH by acting as the key pulmonary vasodilator and modulator (inhibitor) of vasoconstriction in broilers (Khajali and Wideman, 2010).…”
Section: Mediators Of Pulmonary Vasodilationmentioning
confidence: 99%
“…In corn-soybean meal diets that are commonly fed to broiler chickens, methionine and lysine are the first and second limiting amino acids, respectively (Fernandez et al, 1994) and ascorbic acid has shown to be necessary although it is synthesized in bird's body (Attia et al, 2011). Meanwhile, the requirements for amino acids in broilers grown at high altitude regions have been shown to be significantly higher than those published in feeding standards (Basoo et al, 2012;Khajali et al, 2013). In the present study, therefore, L-carnitine was supplemented to a cornsoybean meal diet of broilers exposed to hypobaric hypoxia and looked at beneficial and possible effects with respect to pulmonary hypertensive and immune responses.…”
Section: Introductionmentioning
confidence: 99%